INDIVIDUAL AND COMBINED EFFECTS OF LIFESTYLE BEHAVIORS ON THE HEALTH-RELATED QUALITY OF LIFE OF ADOLESCENTS - Alberto de Moraes, Marcos (Health and Society, 2024)
Background: Identifying lifestyle behaviors that can influence health-related quality of life (HRQoL) in the young population is necessary for the design and implementation of more effective educational and public health interventions. Objective: To investigate the individual and combined effects of a set of lifestyle behaviors, including physical activity, sedentary behavior, sleep and food consumption, on the HRQoL of a sample of Brazilian adolescents. Methods: It is a school-based observational study with the participation of 308 adolescents aged 14 to 18 years. A questionnaire with structured questions was applied to gather demographic and lifestyle behavior data. A healthy lifestyle index was created including positive scores for each individual behavior. HRQoL was measured using the KIDSCREEN-27 questionnaire. Analysis of covariance and linear regression models were used for statistical analysis of the data. Results: Adolescents who reported ≤ 2 hours/day of screen-based sedentary behavior (F = 5.496; p = 0.016) and sleep duration between 8-10 hours/night (F = 6.542; p = 0.009) had significantly higher HRQoL. Adolescents who reported simultaneous adhesion in ≥ 3 healthy lifestyle behaviors demonstrated approximately two [OR = 2.12; 95%CI 1.27 – 4.79] to three times [OR = 3.04; 95%CI 1.93 – 5.62] more odds to have higher perceptions of HRQoL compared to those fulfilling none. Conclusion: Although healthy lifestyle behaviors had a positive individual effect on HRQoL, simultaneous adhesion to healthy behaviors enhances the cumulative effect. The findings reinforce the importance of promoting a healthy lifestyle to ensure HRQoL and well-being in adolescence, with repercussions throughout adulthood.